Inovasi E-Learning Pembelajaran Sejarah (E-PS) Berbasis Web untuk Membangun Keterampilan Guru Abad -21 - Nafi’ah, Ulfatun; S, Leo Agung (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
This research aims to produce web-based history learning e-learning (e-PS) innovation products packaged in the form of Xtended Massive Open Online Courses (xMOOC) to build the skills of 21st century history teachers. This research activity was carried out using the research and development method by Davidson- Shiver and Rasmunssen with stages 1) Analysis, 2) Evaluation Plan, 3) Simultaneous Design which includes design, system development, testing and Implementation and Summative evaluation. This phase can be done many times up to an indefinite time limit; 4) Full Implementation; 5) Summative Evaluation and Research. The data collection technique is in the form of a questionnaire. The type of data used is qualitative and quantitative data. The instrument used in this research was a questionnaire. The questionnaire created was measured using a Likert scale. The data analysis technique uses qualitative descriptive analysis and quantitative descriptive analysis. Based on the total percentage score from media expert validation of 85.27%, and the validation results for material experts of 91.80%, the entire web-based history learning e-learning media is said to be valid without revision.